PENGARUH DAYA TARIK IKLAN DI YOUTUBE TERHADAP BRAND AWARENESS - Rahma Dinti, Novianne; Ira Mirawati; Duddy Zein (Jurnal Netnografi Komunikasi, 2024)
The era of globalization has encouraged rapid advances in internet technology, including the emergence of YouTube social media. YouTube is used as a forum for accessing various types of entertainment videos, exchanging information and promotional tools, especially among generation Z. This strategy is implemented by Marjan products, which always produce advertisements before the arrival of Ramadan. In 2023, the Marjan advertisement will highlight the story of Baruna the Guardian of the Ocean which uses CGI technology effects with an increase in viewership compared to last year and is able to make Marjan the best-selling syrup product (top 1 brand) in Indonesia in Ramadhan 2023. Therefore, this research This was done to find out whether there is an influence and how much influence the Marjan 2023 advertisement on YouTube has on brand awareness among generation Z in Jakarta. This research is quantitative research. The population in this research is viewers of the Marjan 2023 advertisement on YouTube among generation Z who live in Jakarta with a sample size of 100 respondents. The data analysis methods used are Pearson correlation coefficient test analysis, T test, simple linear regression test, and determination test. linear. The conclusion results of this research illustrate that there is an influence of the attractiveness of the Marjan 2023 advertisement on Brand Awareness among generation Z in Jakarta which shows the results of the T test with a significance value of 0.00<0.05. With an influence size of 77.4%, while 22.6% is influenced by other variables not examined in this research.